2014
DOI: 10.1242/dev.110817
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factors and effectors that regulate neuronal morphology

Abstract: Transcription factors establish the tremendous diversity of cell types in the nervous system by regulating the expression of genes that give a cell its morphological and functional properties. Although many studies have identified requirements for specific transcription factors during the different steps of neural circuit assembly, few have identified the downstream effectors by which they control neuronal morphology. In this Review, we highlight recent work that has elucidated the functional relationships bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
72
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 141 publications
(178 reference statements)
0
72
0
Order By: Relevance
“…4,64 For example, in cortical pyramidal neurons the bHLH transcription factor Ngn2 specifies the characteristic primary apical dendrite. 65 The homeodomain factor Cux2 also promotes branch complexity in the apical part of the dendrite arbor, while Cux1 regulates the basal compartment.…”
Section: Microtubule Nucleation Control For Dendrite Morphogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…4,64 For example, in cortical pyramidal neurons the bHLH transcription factor Ngn2 specifies the characteristic primary apical dendrite. 65 The homeodomain factor Cux2 also promotes branch complexity in the apical part of the dendrite arbor, while Cux1 regulates the basal compartment.…”
Section: Microtubule Nucleation Control For Dendrite Morphogenesismentioning
confidence: 99%
“…67 The role of transcription factors in specifying differences in arbor morphology between different types of Drosophila body wall sensory neurons has been extensively studied over the last decade. 4,64 Sensory neuron dendrite patterning is defined by the combinatorial activities of a group of transcription factors, including the homeodomain factor Cut (homolog of Cux1 and 2), the BTB-domain factors Abrupt and Lola, the Kr€ uppellike factor Dar1, the Iroquois factor Mirror, the bHLH-PAS factor Spineless, the PRDM factor Hamlet, and the EBF factor Knot. 41,[68][69][70][71][72][73][74][75][76][77][78] These studies have demonstrated that individual transcription factors control specific aspects of dendrite cytoskeleton organization; for example, Cut and Lola were shown to regulate actin organization, 41,76,78 while Knot, Dar1, and Abrupt regulate microtubule organization.…”
Section: Microtubule Nucleation Control For Dendrite Morphogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Processes of neural network formation are governed by a coupling between activities and cell-to-cell contacts that utilizes numerous proteins including cell adhesion molecules, extracellular matrix proteins and axon guidance molecules, such as ephrins, semaphorins and netrins, 1,2 which are tightly regulated both spatially and temporally during development. 3,4 The membrane association of both Ephs and ephrins enables their unique ability to transduce signals bidirectionally into Eph-expressing cells (forward signaling) and ephrin-expressing cells (reverse signaling) upon cell-cell contact. Ephrin-A and ephrin-B transduce distinct reverse signals upon interaction with their Eph partners acting as ligands and participate in postsynaptic formation.…”
Section: Introductionmentioning
confidence: 99%
“…During this morphogenesis, the cells are organised en masse, and undergo complex, coordinated movement and shape changes. Sophisticated networks of genes are tightly controlled and expressed at predictable times and places, turning on and off at the exact times necessary to choreograph the subsequent development [288]. The brain especially undergoes an amazing array of organisational stages that direct the expansion of the brain from a simple neural tube into an organ with complex internal structures, distinct regions and functions [182].…”
Section: Development and Organizationmentioning
confidence: 99%